Lactose and Lactose Derivatives (IntechOpen, 2021)
Lactose is a unique disaccharide found exclusively in the milk of mammals. This sugar has a crucial role in nourishing newborn and young mammals; however, some adults have difficulties in fully metabolizing lactose. Despite lactose intolerance in the population, the dairy industry produces 400,000 tons of crystalline lactose worldwide. The food and pharmaceutical industries use lactose as well as lactose derivatives in a wide variety of products. This book reviews some aspects of lactose properties and synthesis as well as recent advances in the recovery of lactose and lactose derivatives from cheese whey.